A Theoretical Study of the Adsorption Process of B-aflatoxins Using Pyracantha koidzumii (Hayata) Rehder Biomasses - Abraham Méndez-Albores; René Escobedo-González; Juan Manuel Aceves-Hernández; Perla García-Casillas; María Inés Nicolás-Vázquez; René Miranda-Ruvalcaba (Toxins, 2020)
Employing theoretical calculations with density functional theory (DFT) using the B3LYP/6-311++G(d,p) functional and basis set, the interaction of the aflatoxin B1 (AFB1) molecule and the functional groups present in the Pyracantha koidzumii biosorbent was investigated. Dissociation free energy and acidity equilibrium constant values were obtained theoretically both in solution (water) and gas phases. Additionally, the molecular electrostatic potential for the protonated molecules was calculated to verify the reactivity. Thus, methanol (hydroxyl group), methylammonium ion (amino group), acetate ion (carboxyl group), and acetone (carbonyl group), were used as representatives of the substrates present in the biomass; these references were considered using the corresponding protonated or unprotonated forms at a pH value of 5. The experimental infrared spectrophotometric data suggested the participation of these functional groups in the AFB1 biosorption process, indicating that the mechanism was dominated by electrostatic interactions between the charged functional groups and the positively charged AFB1 molecule. The theoretical determination indicated that the carboxylate ion provided the highest interaction energy with the AFB1 molecule. Consequently, an enriched biosorbent with compounds containing carboxyl groups could improve the yield of the AFB1 adsorption when using in vitro and in vivo trials.